Research on power flux-density at the earth’s surface produced by emissions from the steerable beam of LEO constellation system - Ying HUANG; Wei LI; Chen JIAN; Kang YAN (Dianxin kexue)
The power flux-density (PFD) is an interference criterion for protecting terrestrial service systems from space service systems.A calculation method on the PFD produced by the emissions from the steerable beam of low earth orbit (LEO) constellation system was given, and thus a compliance determination algorithm of the limits of PFD under specific steering angle was presented.On this basis, a compliance determination algorithm of the limits of PFD based on elevation traversal was proposed.Combined with the characteristics of LEO constellation system, the conditions to simplify the calculation of maximum PFD of steerable beam were demonstrated.Taking the Starlink system as the typical scenario, the PFD produced by the gateway beam was analyzed, and the correctness of the proposed method was verified by comparison with the results published by SpaceX.The results showed that the PFD of the gateway beam of the Starlink system in Ka frequency band atelevations below 20° exceeded the limits given in Radio Regulations.